Access, Skills, Economic Opportunities, and Democratic Participation: Connecting Four Facets of the Digital Divide Through Research - Stansbury, Mary (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
In exploring many of the divides that constitute the Digital Divide, this study examines skills, attitudes, and experiences of the individuals most likely to be affected by a lack of computer access and skill. As social scientist Robert Putnam argues, disparities in information and communication technologies access and skills may represent a "cyberapartheid" that diminishes the store. . .